Wiedza o pisarzu w teorii i praktyce szkolnej = Apprehension of the writer in the school theory and practice - Jedliński, Ryszard (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The paper includes the outline of the didactic theory dealing with the apprehension of the writer and its practical applications.
Keywords: dydaktyka literatury